(3GdeSGFd GdCQHYhf GdcdGejIs - (3GdTgjO GdChd , eMeO Hf ecj Hf eMeO Hf MGeO GdYGedj GdfHWj GdLRjfj, TeS GdOjf,J (B786 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3hHYO agPg QSGdI aj GdceSGFd GdcdGejI hVYJgG JbQHkG EdCi HGQj GdHQjI hMUQJgG aj CQHYjf eSCdI s
(3BNQgG (B:s
(3hCNHGQ GdUGOb GdeYdhe HGdUOb hgPG BNQ GdQSGdI hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B109 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B47s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(9/433) s
Keywords: (3GdJhMjO hGdedd hGdfMds